2023
DOI: 10.1109/tcomm.2023.3247753
|View full text |Cite
|
Sign up to set email alerts
|

Joint Location and Beamforming Design for STAR-RIS Assisted NOMA Systems

Abstract: Simultaneously transmitting and reflecting reconfigurable intelligent surface (STAR-RIS) assisted non-orthogonal multiple access (NOMA) communication systems are investigated in its vicinity, where a STAR-RIS is deployed within a predefined region for establishing communication links for users. Both beamformer-based NOMA and cluster-based NOMA schemes are employed at the multi-antenna base station (BS). For each scheme, the STAR-RIS deployment location, the passive transmitting and reflecting beamforming (BF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The STAR-RIS can concurrently reflect and refract the incident signals towards multiple desired MSs. Because of this, the STAR-RIS can further boost the ISAC performance compared to the sole-reflection-type RIS [496], [516], [517] with extended flexibility. Either an outdoor or indoor BS is capable of providing both communications and sensing services to the users located indoors and outdoors by installing a STAR-RIS on a transparent glass window [514], [515].…”
Section: Ris-boosted Thz-isacmentioning
confidence: 99%
“…The STAR-RIS can concurrently reflect and refract the incident signals towards multiple desired MSs. Because of this, the STAR-RIS can further boost the ISAC performance compared to the sole-reflection-type RIS [496], [516], [517] with extended flexibility. Either an outdoor or indoor BS is capable of providing both communications and sensing services to the users located indoors and outdoors by installing a STAR-RIS on a transparent glass window [514], [515].…”
Section: Ris-boosted Thz-isacmentioning
confidence: 99%
“…In [8], to meet the requirements of a more stringent quality-of-service (QoS), STAR-RIS-assisted downlink NOMA networks were investigated. Afterwards, a method of joint optimization for the position and beamforming of STAR-RIS was proposed in [22]. Furthermore, this paper revealed that the optimized position of STAR-RIS could significantly enhance the sum rate.…”
Section: Introductionmentioning
confidence: 99%
“…There are three operation protocols that can control the transmitted and reflected signals: energy splitting (ES), mode switching (MS), and time switching (TS). Thus, many works have been donated to STAR-RIS in recent years [8,[20][21][22][23]. In [20], the performances of three protocols were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In [15], a transmission power minimization problem for the STAR-RIS-aided NOMA system has been studied by jointly optimizing transmission power, transmission and reflection coefficient matrix of the STAR-RIS, and time allocation, which analyzed the interaction between phase shifts and power distribution factor. A weighted sum-rate maximization problem of STAR-RIS assisted NOMA systems has been studied in [16], which has considered respectively beamformer-based NOMA scheme and cluster-based NOMA scheme. Approximate expressions of outage probability and ergodic rate of both imperfect successive interference cancellation (SIC) and perfect SIC schemes have been derived in [17], in which diversity orders are further discussed.…”
Section: Introductionmentioning
confidence: 99%